2012
DOI: 10.1002/chem.201201203
|View full text |Cite
|
Sign up to set email alerts
|

Direct Amidation of Alcohols with N‐Substituted Formamides under Transition‐Metal‐Free Conditions

Abstract: Go tandem! The first example of the direct amidation of alcohols with N‐substituted formamides has been developed. A series of tertiary amides, including the challenging N,N‐dimethyl‐substituted amides, were obtained in moderate to good yields under transition‐metal‐free conditions (see scheme). TBHP=tert‐butyl hydroperoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 97 publications
0
49
0
Order By: Relevance
“…The absence of an amide product with dimethylamine also eliminates the possibility of direct coupling between the acyl and amine radical intermediates (Scheme , b). Depending on the reactants and the catalytic system, various modes for the formation of radicals have been proposed for amide synthesis under oxidative conditions 5b,9,10a,10b. For example, the formation of an amine radical was proposed via tert ‐butyl dimethylcarbamoperoxoate in the direct synthesis of amides from aldehydes and formamides by using Bu 4 NI as the catalyst and TBHP as the oxidant 10a.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of an amide product with dimethylamine also eliminates the possibility of direct coupling between the acyl and amine radical intermediates (Scheme , b). Depending on the reactants and the catalytic system, various modes for the formation of radicals have been proposed for amide synthesis under oxidative conditions 5b,9,10a,10b. For example, the formation of an amine radical was proposed via tert ‐butyl dimethylcarbamoperoxoate in the direct synthesis of amides from aldehydes and formamides by using Bu 4 NI as the catalyst and TBHP as the oxidant 10a.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al reported the direct amidation of alcohols with formamides in the presence of an I 2 /TBHP system in combination with NaOH as a base (Scheme ). [30a] The authors highlighted the role of small amounts of water in the reaction: replacement of aq. TBHP with TBHP in decane led to decreases in the yields of the products.…”
Section: Cdc Of Nn‐disubstituted Formamidesmentioning
confidence: 99%
“…The same authors reported the amidation of benzylamines with formamides in the presence of I 2 /TBHP under acidic conditions (Scheme ). [30b]…”
Section: Cdc Of Nn‐disubstituted Formamidesmentioning
confidence: 99%
“…[51] By utilizing I 2 as the catalyst and H 2 O 2 as the oxidant, different substituted acetophenones and tryptamines could be transformed into the corresponding b-carbolines in good to excellent yields [Eq. (34)]. N otably,t his strategyh as also been successfully applied in the total synthesis of other natural products,s uch as fascaplysin and papaverin.…”
Section: Càibond-formation Reactionsmentioning
confidence: 99%